Diagnostic criteria for temporomandibular disorders in children and adolescents: An international Delphi study‐Part 2‐Development of Axis II. (23rd February 2022) - Rongo, Roberto; Ekberg, EwaCarin; Nilsson, Ing‐Marie; Al‐Khotani, Amal; Alstergren, Per; Rodrigues Conti, Paulo Cesar; Durham, Justin; Goulet, Jean‐Paul; Hirsch, Christian; Kalaykova, Stanimira I.; Kapos, Flavia P.; King, Christopher D.; et al.
Abstract: Background: Unlike the psychosocial assessment established for adults in the Diagnostic Criteria for Temporomandibular Disorders (DC/TMD), a standardised psychosocial assessment for children and adolescents with TMD complaints has not yet been established. Objectives: To develop a new standardised instrument set to assess the psychosocial functioning in children and adolescents by adapting the psychosocial status and pain‐related disability (Axis II) of the adult DC/TMD and by including new instruments. Methods: A modified Delphi method was used to survey 23 international TMD experts and four international experts in pain‐related psychological factors for consensus regarding assessment tools for psychosocial functioning and pain‐related disability in children and adolescents. The TMD experts reviewed 29 Axis II statements at round 1, 13 at round 2 and 2 at round 3. Agreement was set at 80% for first‐round consensus level and 70% for each of the second and third rounds. The psychological experts completed a complementary Delphi survey to reach a consensus on tools to use to assess more complex psychological domains in children and adolescents. For the psychological experts, the first round included 10 open‐ended questions on preferred screening tools for depression, anxiety, catastrophising, sleep problems and stress in children (ages 6–9 years old) and adolescents (ages 10–19 years old) as well as on other domains suggested for investigation. In the second round, the psychological experts received a 9‐item questionnaire to prioritise the suggested instruments from most to least recommended. Results: The TMD experts, after three Delphi rounds, reached consensus on the changes of DC/TMD to create a form to evaluate Axis II in children and adolescents with TMD complaints. The psychological experts added tools to assess depression and anxiety, sleep disorders, catastrophising, stress and resilience. Conclusion: Through international expert consensus, this study adapted Axis II of the adult DC/TMD to assess psychosocial functioning and pain‐related disability in children and adolescents. The adapted Axis II protocols will be validated in the target populations. Abstract : The Delphi process included three rounds and was used to seek international consensus for Axis II assessmentamong 23 TMD experts and 4 experts in psychological domains.Thanks to this Delphi study, experts developednew instruments that aim to assess the psychosocial functioning in children and adolescents by adapting thepsychosocial status and pain‐related disability (Axis II) of the adult DC/TMD.